Islam and Tolerance: The Educational Pattern of Community in Kutuk Village, Kudus - Jihan Avie Yusrina; Syamsul Ma'arif (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
This article expects the readers to witness the condition of religious harmony in the village of Kutuk in Undaan, Kudus, Central Java. The people who live in the village share various religious backgrounds, but they live side by side in harmony. This condition is achieved as the results of the education carried out by the Kutuk people since ancient times that has passed down through generations. Then, what kind of education pattern is being developed by the community to accompany every Muslim to be a tolerant ﬁgure? This research question is answered through a qualitative research with a case study approach that uses non-measurement techniques in data collection processes, namely observation, interviews, and documentation. This study conﬁrms that Kutuk village is a miniature of tolerant village in Kudus district. This village has a lifelong pattern of tolerance education, children with the education in their families, youth with peer education in youth organizations and adults with their educational councils. The methods that were utilized in the process of transmitting the tolerance values are education bil hal (education with good behavior and good examples), education bil maqol (education via oral tradition), and education bil du'a (education with a prayer). These ﬁndings provide some options to the community about applicable steps to empower families and communities in assisting Muslims to be tolerant. It is the evidence in the village that amaliyah of nahdliyyin such as yasinan, tahlilan, and berjanjenan have contributed signiﬁ cantly to educate Muslim to be socially and theologically pious adherents of Islam.